Research and American Industrial Development / A Bicentennial Look at the Contributions of Applied R and D - Vagtborg Harold (Pergamon Press, 1976)
This book has been written for the purpose of relating the influence R&D has had on the phenomenal transformation of a British colony into a world power in the span of 200 years. Foreword, Preface, Acknowledgements, Prologue, Roots of Industrial Research, Stimulating Applied Research in the United States, The Endowed Research Institutes - Mellon and Battelle, The First Non-Endowed Research Institute, The World War Years (1940-1945) and New Institutes, Growth of the Nine Independents, Explosive Growth of Applied Research Institutes, Growth of the Nine Independents, Explosive Growth of Applied Research Institutes, The Fresh Approach, Technology as a Commodity in International Trade, The Research Institutes Abroad, The Federal Government's Role in Research Support, In Retrospect and a Projection of the Future, Appendix, Supplement: ''Highlights of 50 years in R&D Management, Index.